Promotion of online internationalization experiences in physiotherapy students - Alves Lopes, António (2022)
Introduction: Within the scope of the internationalization project of the Escola Superior de Saúde do Alcoitão (ESSAlcoitão), a set of activities are developed along the academic path of the students, which allow them to be exposed to the international context sequentially and progressively. Methodoloy: During the 2020/21 academic year, ESSAlcoitão, in partnership with 3 institutions in the Netherlands, implemented a project involving students from the 1st year of the Physiotherapy Course. In this project, students are asked, over 3 months, to carry out at least 2 online meetings with an international partner to discuss topics related to the reality of teaching and the practice of Physiotherapists. As a result, students submit an individual reflection on the most relevant points that were identified in this sharing process. In each of the participating institutions, there was a teacher responsible for preparing, supporting, and evaluating the students' reflections. Results: To assess the impact (satisfaction) with 1st-year students at ESSAalcoitão, an online questionnaire (22 questions) was used, with several dimensions (preparation, performance, evaluation, and global opinion) where a response rate of 98% was obtained (n=61). Regarding the answers, 93.4% considered that the preparation of the activity was adequate and that the support materials were adequate (85.2%). Regarding meetings with international peers, 70.2% said that communication was easy during the meetings and that the proposed objectives were achieved (91.2%). Concerning the impact of the activity, 91.8% considered that the activity contributes to a better understanding of the international context of teaching and practice of physiotherapists, stressing that it should continue to be carried out within the scope of the course (88.5%). Conclusions: Because of the results, it seems important to us to carry out this type of activity as it allows students early exposure to the international context, which may facilitate the development of skills that allow them to play a more active and global professional role.